2016
DOI: 10.1002/2016gl070776
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of cloud fraction profile in shallow convection using a scanning cloud radar

Abstract: Large spatial heterogeneities in shallow convection result in uncertainties in estimations of domain‐averaged cloud fraction profiles (CFP). This issue is addressed by using large eddy simulations of shallow convection over land coupled with a radar simulator. Results indicate that zenith profiling observations are inadequate to provide reliable CFP estimates. Use of scanning cloud radar (SCR), performing a sequence of cross‐wind horizon‐to‐horizon scans, is not straightforward due to the strong dependence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 35 publications
(40 reference statements)
1
28
0
Order By: Relevance
“…For example, a recent study by Oue et al (2016) has shown that zenith-pointing observations from one location are inadequate to provide reliable cloud fraction profile estimates in a cumulus field. A similar investigation on 3D wind retrievals in deep convection using multi-Doppler radar techniques highlights similar deficiencies of our current observing systems (Oue et al, 2019a). How do we best quantify the measurement uncertainty introduced by the observational strategy?…”
Section: Introductionmentioning
confidence: 73%
“…For example, a recent study by Oue et al (2016) has shown that zenith-pointing observations from one location are inadequate to provide reliable cloud fraction profile estimates in a cumulus field. A similar investigation on 3D wind retrievals in deep convection using multi-Doppler radar techniques highlights similar deficiencies of our current observing systems (Oue et al, 2019a). How do we best quantify the measurement uncertainty introduced by the observational strategy?…”
Section: Introductionmentioning
confidence: 73%
“…There are several limitations when designating cloud boundaries and hourly CF observations from vertically pointing cloud radars beyond the capabilities of single radar platforms or ARSCL methods (e.g., Lamer and Kollias, 2015;Oue et al, 2016). The primary limitation among these is that the WACR experiences attenuation in rain that manifests as erroneously low or missing cloud-top boundaries (e.g., Feng et al, 2009Feng et al, , 2014.…”
Section: Radar Dataset and Multi-sensor Mergingmentioning
confidence: 99%
“…A scanning, S-band, radar operated by the Barbados Meteorological Service can be used for research purposes in the absence of severe weather. It will help characterize the mesoscale organization of convection, and the vertical structure of the shallow cloud cover (Nuijens et al 2009;Oue et al 2016). The deployment of a second C-Band radar, the POLDIRAD of the Institut für Physik der Atmosphäre at the Deutschen Zentrum für Luft-und Raumfahrt, is also being considered.…”
Section: Surface and Ship-based Observationsmentioning
confidence: 99%
“…Another one will consist in analysing data from ground or ship-borne instruments. Ceilometers will be very useful, but a scanning radar (Oue et al 2016) on one of the research vessels or deployed on Barbados is also being considered. Yet another approach will consist of analysing observations from the SpecMACs instrument on HALO.…”
Section: Estimating the Distribution Of Clouds In The Trade-wind Bounmentioning
confidence: 99%